Digitalized mass distribution campaign of insecticide-treated nets (ITNs) in the particular context of Covid-19 pandemic in Benin: challenges and lessons learned - Aïkpon, Rock; OGOUYEMI -HOUNTO, Aurore (My University, 2020)
Background: In 2020, Benin has implemented a digitalized mass distribution campaign of insecticide-treated nets (ITNs) in the particular context of COVID-19 pandemic. This paper describes the implementation process as well as the challenges and lessons learned from this campaign. Methods: A descriptive design was used for reporting the planning and implementation process of ITNs campaign. Moreover, the changes and adaptations related to COVID-19 pandemic are described. Results: A total of 3,175,773 households were registered corresponding to a total of 14,423,998 persons (13.55% more from projection). Moreover, 94.16% (13,581,637 people) of enumerated population were protected. A total of 7,652,166 ITNs were distributed countrywide. Conclusions: High political commitment, engagement and support add to the fnancial and technical supports from partners were the essential factors that make 2020 ITNs mass campaign success in Benin despite the particular con text of COVID-19 pandemic. It is essential to maintain the prevention activities for malaria and this could substantially reduce the overall impact of the COVID-19 pandemic for the populations at malaria risk.
Keywords: Digital; Itns campaign; Covid-19; Lessons; Benin